The Big Con: How the Consulting Industry Weakens our Businesses, Infan tilizes our Governments and Warps our Economies - Mazzucato, Mariana; Collington, Rosie (Allen Lane, 2023)
There is an entrenched relationship between the consulting industry an d the way business and government are managed today which must change. Mariana Mazzucato and Rosie Collington show that our economies' relian ce on companies such as McKinsey, Boston Consulting Group, Bain & Comp any, PwC, Deloitte, KPMG and EY stunts innovation, obfuscates corporat e and political accountability and impedes our collective mission of h alting climate breakdown.The 'Big Con' describes the confidence trick the consulting industry performs in contracts with hollowed-out and ri sk-averse governments and shareholder value-maximizing firms. It grew from the 1980s and 1990s in the wake of reforms by both the neoliberal right and Third Way progressives, and it thrives on the ills of moder n capitalism, from financialization and privatization to the climate c risis. It is possible because of the unique power that big consultanci es wield through extensive contracts and networks - as advisors, legit imators and outsourcers - and the illusion that they are objective sou rces of expertise and capacity. To make matters worse, our best and br ightest graduates are often redirected away from public service into c onsulting. In all these ways, the Big Con weakens our businesses, infa ntilizes our governments and warps our economies.Mazzucato and Colling ton expertly debunk the myth that consultancies always add value to th e economy. With a wealth of original research, they argue brilliantly for investment and collective intelligence within all organizations an d communities, and for a new system in which public and private sector s work innovatively for the common good. We must recalibrate the role of consultants and rebuild economies and governments that are fit for purpose.